ACUTE EFFECT OF TWO TYPES OF RECOVERY IN THE SWIMMERS BLOOD LACTATE FOLLOWING MAXIMUM EFFORT (Fiep Bulletin - online, 2014)
Objectives: To identify the acute effect of passive recovery and active recovery on blood lactate after maximal exercise, as well as demonstrating the lactate kinetics in these two types of recovery. Methods: The sample consisted of 15 swimmers with a mean age 15-20 years who participated in two experimental procedures. In the first, after conducting a simulation proof of competitive 200 meter freestyle, performed passive recovery of 15 minutes in the supine position. In the second procedure, after the same simulation competitive athletes performed five minutes of passive recovery, supine, necessitated by the blood collection, and 10 minutes of active recovery at 60% - 65% intensity, according to the ability of each athlete. During passive recovery, athletes remained protected from the sun, in a covered place. 3 collections were made about 1 - 2 drops of blood in each procedure occurring before simulation competitive 5 minutes after and 15 minutes after, the two procedures. Results: In the collection held prior to competitive simulation, there was no significant difference (p
Keywords: Recovery; lactate; swimming.